A STUDY ON SATISFACTION, PERCEPTION AND EXPECTATION LEVEL OF INSTITUTIONAL CONSUMERS TOWARDS PAINT BRANDS IN AL-KHARJ REGION, KINGDOM OF SAUDI ARABIA - Teg Alam; Mohammad Rishad Faridi (European Scientific Journal, ESJ, 2014)
Paint marketing has transitioned as a commodity to a consumer product, which spurs marketers to be proactive in chalking strategies to enable them to have competitive advantage. Consumer is largely categorized into two major segments i.e. consumer market and institutional market. This research paper explores expectation, perception and satisfaction level of institution segment which comprises mainly of painters, contractors etc. Paint companies are emphasizing in creating and building long term relationship. On the other hand institutional consumers look for brands which have quality, better service and more important competitive price. Al Kharj is a city of future in the Kingdom of Saudi Arabia, growing socially and economically at a rapid speed. Paint brands are eyeing this rich market as it grows. In paint, price war which is a tool in gaining business in bulk segment, companies are also collaborating with the paint professionals for technical support, preparing feasibility report, guidance in project management in perspective of paint product. This research paper will help paint companies to understand where they are currently and where they are supposed to go with understanding their competitors marketing plan especially in Al Kharj region. A gap analysis will be a further scope of research in paint business.